A rare reason of the elevated serum Ca 19-9 and Ca 125 levels in neonatal period: Hydrometrocolpos due to distal vaginal atresia. (2015) - Celik, Muhittin; Bulbul, Ali; Uslu, Sinan; Dursun, Mesut; Turkoglu, Ebru; Sever, Nihat
Highlights: Hydrometrocolpos is a rare congenital malformation of the female in neonate. CA 19-9 and CA 125 are widely used as tumor markers, however several benign conditions are also known to increase levels. Here we report a newborn with hydrometrocolpos due to distal vaginal atresia and elevated serum CA 19-9 and CA 125 levels.